VD_FINDINFO Décision / 2014 / 34 vom 27. November 2013 - VD Tribunal cantonal (2013)
EXPERTISE PSYCHIATRIQUE, RÉCUSATION, DÉCISION D'IRRECEVABILITÉ | 393 al. 1 let. b CPP (CH), 428 al. 1 CPP (CH), 56 CPP (CH), 59 CPP (CH)